Analysis of primary creep in simulated heat affected zone (HAZ) of two 9 - 12% Cr Steel grades - F. Kafexhiu; F. Vodopivec; B. Podgornik (Metalurgija, 2017)
The primary creep of the parent metal (α), inter-critical (α+γ), and coarse-grained (γ) microstructures of simulated weld heat-affected zone (HAZ) for the steels X20CrMoV121 and X10CrMoVNb91, aged for 4 320 hours (6 months) at 750 °C and 17 520 hours (2 years) at 650 °C was analyzed. The time and creep strain at the transition point from primary to secondary creep were found to vary strongly between the parent metal and two simulated HAZ microstructures, especially after ageing at 750 °C.